2012
DOI: 10.1080/15299732.2012.694841
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Young Adults' Progress in Treatment for Dissociative Disorder

Abstract: Although treatment outcome research on dissociative disorders (DD) is increasing, an examination of treatment progress in young adults with these disorders remains noticeably absent from the literature. Many studies of DD patients report mean ages over 35. The present study examined the response to treatment of a subsample of young adults ages 18-30 with dissociative identity disorder and dissociative disorder not otherwise specified who participated in a naturalistic, longitudinal study of DD treatment outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Indeed, the clinical utility of targeting dissociation has already been demonstrated by Myrick et al (2012), who found that in a naturalistic study, "self-destructive behaviour" reduced following treatment for dissociative disorders in a sample of 18 to 30 year olds. An expansion of this research into the adolescent age range-with the specific objective of reducing ADSH-would be useful to clinicians working with these presentations.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the clinical utility of targeting dissociation has already been demonstrated by Myrick et al (2012), who found that in a naturalistic study, "self-destructive behaviour" reduced following treatment for dissociative disorders in a sample of 18 to 30 year olds. An expansion of this research into the adolescent age range-with the specific objective of reducing ADSH-would be useful to clinicians working with these presentations.…”
Section: Discussionmentioning
confidence: 98%
“…Because these participants demonstrated improvements in dissociative, posttraumatic, and depressive symptoms, decreased rates of hospitalization and suicidality, and increased adaptive functioning over the course of the study (e.g. Brand & Loewenstein, 2014; Brand et al, 2013; Brand & Stadnik, 2013; Myrick et al, 2012), we hypothesized that inpatient and outpatient treatment estimated costs would decrease over time. Furthermore, we expected that patients in the earlier stages of treatment, who struggle with safety issues such as self-injurious behaviour and suicidality (e.g.…”
Section: Highlightsmentioning
confidence: 99%
“…Delay in recognition and adequate treatment of DID likely prolongs the suffering and disability of DID patients. Younger DID patients appear to respond more rapidly to treatment than do older adults, 167 which suggests that years of misdirected treatment exact a high personal cost from patients. 166 Needless to say, if clinicians do not recognize the disorder, they cannot provide treatment consistent with expert guidelines for DID.…”
Section: The Cost Of Myths and Ignorance About Didmentioning
confidence: 99%